Jensen m-Convexity on Set-Valued Function - Pramana, Eko Dedi; Wibowo, Ratno Bagus Edy; Muslikh, Mohamad (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
This paper discusses the class of Jensen m-convex functions and their properties, leading to enhancements of these functions and Jensen's inequalities for set-valued functions. It provides several characterizations and explores various algebraic properties. Additionally, it introduces a discrete Jensen-type inclusion.